Spinney: Post-processing of first-principles calculations of point defects in semiconductors with Python - Arrigoni, Marco; Madsen, Georg K.H. (Computer physics communications, 2021)
Understanding and predicting the thermodynamic properties of point defects in semiconductors and insulators would greatly aid in the design of novel materials and allow tuning the properties of existing ones. As a matter of fact, first-principles calculations based on density functional theory (DFT) and the supercell approach have become a standard tool for the study of point defects in solids. However, in the dilute limit, of most interest for the design of novel semiconductor materials, the “raw“ DFT calculations require an extensive post-processing. Spinney is an open-source Python package developed with the aim of processing first-principles calculations to obtain several quantities of interest, such as the chemical potential limits that assure the thermodynamic stability of the defect-laden system, defect charge transition levels, defect formation energies, including electrostatic corrections for finite-size effects, and defect and carrier concentrations. In this paper we demonstrate the capabilities of the Spinney code using c-BN, GaN:Mg, TiO2 and ZnO as examples. Program Title:Spinney CPC Library link to program files:https://doi.org/10.17632/2xp4ddwmgx.1 Developer’s repository link:https://gitlab.com/Marrigoni/spinney Code Ocean capsule:https://codeocean.com/capsule/4970623 Licensing provisions: MIT Programming language: Python 3 External libraries: NumPy [1], SciPy [2], Pandas [3], Matplotlib [4], ASE [5] Nature of problem: Post-processing of first-principles calculations in order to obtain important properties of defect laden systems in the dilute-limit: chemical potential values ensuring thermodynamic stability, thermodynamic charge transition levels, defect formation energies and corrections thereof using state-of-the-art corrections schemes for electrostatic finite-size effects, equilibrium defect and carriers concentrations. Solution method: Flexible low-level interface for allowing the post-processing of the raw fist-principles data provided by any computer code. High-level interface for parsing and post-processing the first-principles data produced by the popular computer codes VASP and WIEN2k. Additional comments including restrictions and unusual features: An extensive documentation is available at: https://spinney.readthedocs.io